2016
DOI: 10.1111/jpn.12648
|View full text |Cite
|
Sign up to set email alerts
|

Preference of goats (Capra hircus L.) for tanniniferous browse species available in semi‐arid areas in Ethiopia

Abstract: The objectives were to determine browse species preference of goats using dry matter intake (DMI) as a proxy, to compare preference when offered in combination with polyethylene glycol (PEG) and to establish relationships between browse species intake and chemical compositional data. Air-dried leaves of Acacia etbaica, Cadaba farinosa, Capparis tomentosa, Dichrostachys cinerea, Dodonaea angustifolia, Euclea racemosa, Maerua angolensis, Maytenus senegalensis, Rhus natalensis and Senna singueana were used. Two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…CT from sainfoin exhibited anthelmintic properties against exsheathment of H. contortus in vitro and in vivo in sheep (Brunet et al, 2007). The browse plant species used in the present study have been reported to be voluntarily consumed by goats (Yayneshet et al, 2008;Mengistu et al, 2016) and at optimal intake, may exhibit anthelmintic activity against H. contortus. Anthelmintic properties of the browse plant species, however, have to be examined under practical farming conditions before foreseeable future practical application to control H. contortus to improve productivity and health of goats in the study area and for wider application in similar regions.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…CT from sainfoin exhibited anthelmintic properties against exsheathment of H. contortus in vitro and in vivo in sheep (Brunet et al, 2007). The browse plant species used in the present study have been reported to be voluntarily consumed by goats (Yayneshet et al, 2008;Mengistu et al, 2016) and at optimal intake, may exhibit anthelmintic activity against H. contortus. Anthelmintic properties of the browse plant species, however, have to be examined under practical farming conditions before foreseeable future practical application to control H. contortus to improve productivity and health of goats in the study area and for wider application in similar regions.…”
Section: Discussionmentioning
confidence: 56%
“…This information allows comparisons of anthelmintic properties of polyphenols from different plant sources and across studies. The browse plant species in the present study grow in semi-arid areas (Bein et al, 1996) and are readily consumed by goats in these areas (Yayneshet et al, 2008;Mengistu et al, 2016). However, their anthelmintic properties against goat nematodes are unknown.…”
Section: Introductionmentioning
confidence: 94%
“…Bite count is a direct measurement with a long tradition in foraging behaviour research [26,27]. This method has been chosen for its ease of application in the field and because it does not require the estimation of the dry weight that is applied in the determination of preferences based on the difference between intake and rejection.…”
Section: Bite-count Proceduresmentioning
confidence: 99%
“…Leaves of Acacia etbaica, Cadaba farinosa, Capparis tomentosa, Dichrostachys cinerea, Dodonaea angustifolia, Euclea racemosa, Maerua angolensis, Maytenus senegalensis, Rhus natalensis and Senna singueana were collected by hand-clipping from two area exclosures (protected areas allowed to rest from human and animal intervention) in the Tigray region of Ethiopia in October 2014. The browse species are voluntarily consumed by goats from the same region (Mengistu et al, 2016). From each exclosure, leaves were collected from 15 phenologically similar plants per species, bulked into one sample per species and air-dried in an open shed.…”
Section: Browse Species Collection and Preparationmentioning
confidence: 99%
“…Regardless of previous exposure to tannins, the saliva of goats is high in proline-rich proteins (Ventura-Cordero et al, 2015). This adaptation enables goats to voluntarily consume substantial quantities of tannin-containing browse species (Yayneshet et al, 2008;Mengistu et al, 2016) commonly found in semi-arid areas.…”
Section: Introductionmentioning
confidence: 99%